Studying the Effect of MgO Addition on the Thermal and Electrical Properties for Iraqi Porcelain - Mahdi, Duraid Fawzi (Al-Nahrain Journal of Science, 2017)
The research was studied effect of addition Magnesium Monoxide (MgO) on the thermal and electrical properties of Iraqi Porcelain with different weight percentages were (0%, 5%, 10%, 17%, 23% and 30%). The Porcelain was hard type and consist of (50%wt) Kaolin, (25%wt) Potassium Feldspar and (25%wt) Flint and sieving process was achieved for all powders and the particle sizes were (